2021
DOI: 10.1002/clt2.12037
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis on allergen‐specific immunotherapy using MCT® (MicroCrystalline Tyrosine)‐adsorbed allergoids in pollen allergic patients suffering from allergic rhinoconjunctivitis

Abstract: Background The World Allergy Organization and the European Academy of Allergy and Clinical Immunology recommend to perform product‐specific meta‐analyses for allergen‐specific immunotherapies because of the high degree of heterogeneity between individual products. This meta‐analysis evaluates the efficacy and safety of Glutaraldehyde‐modified and MCT® (MicroCrystalline Tyrosine)‐adsorbed allergoids (MATA). Methods The databases MEDLINE, LILACS, embase, LIVIVO, Web of Science and Google (Scholar) were searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
(208 reference statements)
0
13
0
Order By: Relevance
“…MCT has not shown toxic properties, although it is contraindicated in tyrosine metabolism disorders [ 90 ]. Currently, MCT is patented as an adjuvant for use in immunotherapy [ 93 ] and is integrated into glutaraldehyde allergoids for Dermatophagoides to help reduce allergic symptoms and diminish the use of relief drugs [ 94 , 95 , 96 , 97 ].…”
Section: Adjuvantsmentioning
confidence: 99%
“…MCT has not shown toxic properties, although it is contraindicated in tyrosine metabolism disorders [ 90 ]. Currently, MCT is patented as an adjuvant for use in immunotherapy [ 93 ] and is integrated into glutaraldehyde allergoids for Dermatophagoides to help reduce allergic symptoms and diminish the use of relief drugs [ 94 , 95 , 96 , 97 ].…”
Section: Adjuvantsmentioning
confidence: 99%
“…As Allergoid-MCT has been marketed for decades, many clinical studies including DBPC trials have been conducted since their introduction on the market. A recently published meta-analysis undertaken by Becker et al [ 33 ▪ ] provides an overview about the evidence generated since the 1970s. These data formally fulfil the highest standard for the level of evidence (1A) according to the European Academy of Allergy and Clinical Immunology (EAACI), because they are based on a systematic literature review and meta-analysis [ 34 ].…”
Section: Evidence From Double-blind Placebo-controlled Trialsmentioning
confidence: 99%
“…These data formally fulfil the highest standard for the level of evidence (1A) according to the European Academy of Allergy and Clinical Immunology (EAACI), because they are based on a systematic literature review and meta-analysis [ 34 ]. It is focused on MCT-adsorbed pollen allergoids and clearly demonstrates a significant improvement in allergic symptoms and a reduction in the use of antiallergic medication when compared with placebo, together with an excellent safety profile [ 33 ▪ ]. The analysis included, among other randomized controlled trials (RCTs), controlled trials and noncontrolled studies, eight double-blind placebo-controlled trials (DBPCs) with a total of 884 patients with seasonal allergic rhinoconjunctivitis.…”
Section: Evidence From Double-blind Placebo-controlled Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, allergen immunotherapy (AIT) has been used for the treatment of allergic rhinitis and rhinoconjunctivitis, asthma, and venom allergy. At present, AIT is supported by data accumulated from large, double-blind, placebo-controlled clinical trials demonstrating efficacy and safety [4][5][6][7][8][9][10][11], as well as a high number of noninterventional studies, systematic reviews and meta-analyses [12][13][14], and real-world evidence [15][16][17][18][19]. Among its benefits, it has been demonstrated that AIT may prevent the development of asthma in children with allergic rhinitis [8].…”
Section: Introductionmentioning
confidence: 99%